1990
DOI: 10.1039/ft9908601503
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle neutron scattering study of D2O–alcohol solutions

Abstract: Small-angle neutron scattering (SANS) measurements have been carried out on heavy water solutions of ethanol, isopropyl alcohol, n-propyl alcohol, t-butyl alcohol and butoxyethanol between 5 and 37 "C at t h e concentrations where ultrasonic attenuation exhibits peak values. The wavevector dependence and the absolute intensity of the scattered intensities were analysed according to a microscopic model of t h e solutions in terms of aggregated complexes. The results indicate that at 25 "C there exist either alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 25 publications
6
46
0
Order By: Relevance
“…1b) show coherent structure, with larger correlation lengths present in pyridine solutions, corresponding to clusters of tens to hundreds of molecules, while the small correlation length for the isopropanol implies aggregates of only a few molecules, as would be expected. The presence of structure in these solutions is consistent with previous SANS experiments 46-48. When 3 molal GdmCl is added to isopropanol (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1b) show coherent structure, with larger correlation lengths present in pyridine solutions, corresponding to clusters of tens to hundreds of molecules, while the small correlation length for the isopropanol implies aggregates of only a few molecules, as would be expected. The presence of structure in these solutions is consistent with previous SANS experiments 46-48. When 3 molal GdmCl is added to isopropanol (Fig.…”
Section: Resultssupporting
confidence: 91%
“…For this reason, it is not possible to determine simultaneously the exact composition of the clusters and the concentration of the clusters. This has been described previously by D’Arrigo and Teixeira,46 who showed that micelle-like clusters of solute in D 2 O or water-solute aggregates in the remaining water and solute monomers are the two most likely structures present in solution.…”
Section: Resultssupporting
confidence: 71%
“…Subsequent DLS measurements in the temperature range 283 ≤ T/K ≤ 313 indicated that contamination in BE samples might have led to formation of such large diffusers, and for contaminationfree samples, the estimated correlation lengths were in general agreement with those from neutron 2-6 and light scattering measurements. 23 The scenario becomes even more complex with SANS measurements 5,6 reporting rapid growth of the correlation length with the solution temperature approaching T c . In addition, scaling laws related to critical phenomena appeared to explain the considerable slowing down of diffusivities in these mixtures as critical concentration (X BE c ) and temperature (T c ) were approached.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular dynamics simulations have shown the presence of micelle-like fluctuations over a dilute concentration range, 3 mol % to 8 mol % (11 mass % to 26 mass %) TBA in water [7]. Numerous experimental studies and other simulations support this picture [14][15][16][17][18][19][20]. Micelle-like structural fluctuations lead to anomalies in the thermodynamic properties of TBA-water solutions [7].…”
Section: Introductionmentioning
confidence: 99%